PENERAPAN MODEL COURSE REVIEW HORAY TERHADAP HASIL BELAJAR SISWA PADA POKOK BAHASAN KPK DAN FPB - Dwi Cahyadi Wibowo; Rusdi Rusdi; Cici Wahyuni; Sirilus Sirhi (STKIP Persada Khatulistiwa Sintang, 2023)
This research is aims to determine the application of the course review horay model to the learning outcomes of class IV students on the subject matter of the KPK and FPB. The research conducted by quasy experimental design through nonequivalent control group design. The population in this study were all fourth grade students of the State Elementary School 08 Kenyauk consisting of IVA and IVB. The sample in this study was class IVA as the experimental class with a total of 21 people and class IVB as the control class with a total of 22 people. Data collection techniques used measurement techniques, with test used as the data collection. The results showed thats 1)there is a significant difference in student learning outcomes in the pretest and posttest experimental class 2) there is a significant difference in student learning outcomes in the pretest and posttest control class, and there is a significant difference in student learning outcomes in the post-test between the experimental class and the control class. It can be concluded that the Course Review Horay learning model has an effect on student learning outcomes on the KPK and FPB material in grade IV SD Negeri 08 Kenyauk.